A socioeconomic history of North Korea (McFarland & Co., 2011)
"Even as its rise as a nuclear power unfolds on the nightly news, North Korea remains arguably the most mysterious country in the world. This groundbreaking study offers the first comprehensive examination of the social and economic history of North Korea from its founding in 1948 to the present day"--Provided by publisher.